Private Business Valuation Practical case of RecoveryLabs - Terechowicz Schmidt Robert (My University, 2008)
The main purpose of this research is to valuate, or in other words to find a proper value of RecoveryLabs, a Spanish privately owned company based in Madrid, operating within the IT sector. After a short description of the company I will summarize the broad theory of business valuation with its different approaches to the problem, and later on I will choose the one which best suits the case of RecoveryLabs. The biggest influence on the choice will have the fact, that the company is not publicly traded, which has its consequences at each stage of the valuation process. It also means that the sought value of the business or value of the equity stake in the company will be its “intrinsic” value with no possibility to compare it with its market value. The access to the real accounting data of RecoveryLabs was possible because of the fact that autor used to work there shortly during the summer of 2006 and Managers of the company did not have any objections to provide with necessary data I needed for the purpose of this research. Unfortunately I could not have at my disposal Cash Flow statements of the company which meant some additional challenge. The data related to other companies in the sector had to be partly researched on my own, mainly on-line. Any financial data about stock listed firms in the sector is quite easily accessible, as those companies are obligated by law to provide a series of information to the market.
Wycena Małej Firmy na przykładzie RecoveryLabs
Keywords: the company; the market; valuation methods; cash flow; company valuation; valuing private firms